Pendampingan Asuhan Keperawatan Medikal Bedah pada Pasien dengan Gangguan Sistem Persyarafan: Fraktur Lumbal - Nur Hidayat; Noneng Nuraida (Yayasan Inspirasi El Burhani, 2022)
Introduction: Lumbar fracture is a disease of the nervous system where the continuity of the lower spine is broken. Lumbar fractures can be caused by predisposing factors such as traffic accidents or falls, as well as precipitating factors such as obesity and lack of calcium intake that cause low bone density. Objective: This assistance is aimed at providing nursing care to Mrs. M with a medical diagnosis of a lumbar fracture in the Famboyan room of the Banjar City Hospital in 2021. Method: This assistance activity is carried out by providing nursing care with five stages of the nursing process, including assessment, diagnosis, nursing planning, nursing implementation and results. Result: The results of the assistance showed that the patient's main complaint was low back pain, the diagnosis that emerged in the patient was acute pain, after being given nursing actions from 6-10 December with the results the patient said the pain scale had decreased slightly, the patient looked more relaxed. Conclusion: After giving the nursing care process which was carried out on December 6-10 2021, the problems found in Mrs. M with a medical diagnosis of a lumbar fracture that has not been resolved.